Adoption of a Comprehensive Web-Based Wealth Management Service - Tomi Dahlberg; Anssi öörni (IGI Global, 2022)
The design of electronic financial services differ crucially from that of conventional services due to their inability to adjust sporadically to the needs and wants of consumers, as adaptability is strongly associated with the human component of services production. In this regard, identification of the motives driving adop- tion and consumption is the precondition for successful implementation of electronic services. This article reports the results of a survey conducted for an R&D project with the objective to design an innovative and comprehensive wealth management service for consumers, a service that is offered mainly via the internet. In this study, the authors found that the conventional wisdom of mainstream finance and technology adoption theories, return-risk thinking, and cost-benefit analysis of product characteristics were insufficient to predict adoption. Rather, the adoption decision appears to be dominated by the perceived fit between the new service and the consumer’s established consumption patterns.